Sleep and affect assessment, theory, and clinical implications - Babson, Kimberly A. (Kimberly Anne) 1983-; Feldner, Matthew T. (Academic Press, 2015)
This book will be of use to sleep researchers, affective neuroscientists, and clinical psychologists in order to better understand the impact of emotion on sleep as well as the effect of sleep on physical and mental well-being. Contains neurobiological, cognitive, and behavioral approachesExplains methods for examining sleep and affectSummarizes research on sleep and specific affect statesTranslates research for clinical use in treating disorders"